Strain hardening, twinning and texture evolution in magnesium alloy using the all twin variant polycrystal modelling approach. (May 2020) - Sahoo, Sudeep K.; Biswas, Somjeet; Toth, Laszlo S.; Gautam, P.C.; Beausir, Benoît
Abstract: In this work, the viscoplastic self-consistent based All Twin Variant (ATV) polycrystal modelling was employed to decipher the deformation behaviour of Mg–3Al-0.3Mn Magnesium alloy that develops 10 1 ‾ 2 1 ‾ 011 - extension twins profoundly during ambient temperature compression. Twinning was considered by taking into account all the potential 10 1 ‾ 2 − twin variants, and hence called here as the 'ATV' approach. The model treats each twin variant as a grain with increasing volume fraction transferred from the respective parent grain according to its pseudo-slip shear-rate. The slip and twin-induced strain hardening were simulated by adopting a classical phenomenological hardening model while assigning a higher hardening coefficient for the twins relative to the parent matrix. The viscoplastic self-consistent polycrystal homogenisation scheme combined with the ATV approach permitted to reproduce with high precision the experimentally measured strain hardening behaviour, crystallographic texture and twin volume fraction evolution. Beyond these average measures, the activities of twin variants in individual grains could be predicted in good agreement with Electron Back-Scattered Diffraction measurements. The ATV approach permits also to examine the matrix and twin phases separately in terms of textures and misorientation distributions. Graphical abstract: Image 1 Highlights: All twin variants were used as grains within the VPSC approach in compression of Mg. Strain hardening, twin volumes, and texture evolutions were simulated with precision. The model reproduces the volume fractions of all twin variants in individual grains. The major effect on twin activity is crystal orientation, not the neighbouring grains. Intersecting or parallel twin configurations were explained by variant selection.